(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper, we have discussed various parallel scheduling algorithms and there drawbacks. Out of static scheduling algorithms the Dynamic Critical Path (DCP) Algorithm is the best algorithm. It has an admissible time complexity, is economical in terms of the number of processors used and is suitable for a wide range of graph structures. But multiprocessor scheduling problem is NP-complete in nature even with simplifying assumptions, and becomes more complex under relaxed assumptions such as arbitrary precedence constraints, and arbitrary task execution and communication times. Therefore, a Genetic approach based algorithm was proposed with an objective to simultaneously meet the goals of high performance, scalability, and fast running time known as Parallel Genetic Scheduling (PGS) algorithm. And even outperforms DCP algorithm best known in terms of performance and time complexity.